The Teknik Pemasangan Kateter Pada Kejadian Infeksi Saluran Kemih Di Ruang Rawat Inap RSUD Pringsewu - Diny Vellyana; Gunawan Irianto; Rahmad Rahmad (Jurnal Kesehatan Indonesia, 2020)
Urinary catheterization is an action to insert a catheter into the bladder through the urethra, this is done only in a situation because there is a risk of microorganism entering the bladder and urinary tract. The objective of this research to know the corelations the catheter installation technique with the incidence of urinary tract infections at Pringsewu General Hospital in 2019, with determination of urinary tract infections using only assessment points on body temperature, urine consistency and pain. The research design used analytical survey with a cross sectional approach. The number of samples are 28 people. This research used univariate and bivariate analysis. The results showed that there is a relationship the catheter installation technique with the incidence of urinary tract infections at Pringsewu General Hospital in 2019, the results of statistical tests were obtained p-value = 0.004 <Î± = 0.05. The researcher assessed to nurses be able of maintain the correct catheterization procedure in accordance with the procedure especially to wash their hands before and after catheter installation, and assessment of urinary tract infections should be supplemented with laboratory results.